PERFORMANCES OF TWO PROTOTYPES OF LOG EXTRACTION TECHNIQUES USING THE SKYLINE SYSTEM - Wesman Endom; Satria Astana (Indonesian Journal of Forestry Research, 2017)
Timber extraction from felling area to road side is not an easy job. This activity facing a number of  difficulties particularly due to geo-biophysical conditions, such as steep terrain, up and/or down-hill, valley or river-to be crossed, slippery road and also the size of the timber and low accessibility. To anticipate those obstacles two engineering designs of the skyline system had been tried, the so called Expo-2000 Generation-1, using gasoline engine of  6 HP (G-1), and Expo-2000 Generation-3 using dieselengine of  12 HP (G-3). G-1 model has been tested in Cimeong and Rancaparang in 2011. G-3 model has been examined in Cibatu Canjur and Cibaliung Banten in 2013. This paper evaluates the modification of skyline system for steep terrain and to compare the performance between two modified skyline systems, in term of productivity and cost. The data collected included working time, log volume extracted, log extraction distance and fuel used. Data were analyzed to get the average productivity and cost of operation. Result show that prototype G-3 with logs in horizontal position at a distance of  130-430 m, can extract logs averaging 1.72 m3/hr, at a cost of  about Rp 80,346/m3, while prototype G-1 and logs in vertical position at a  distance of  about 50-320 m, could only extract logs averaging ± 0.85 m3/ hr at a cost of about Rp 156,351/m3. It suggests that prototype Expo-2000 G-3 is more effective for log extraction logs in steep terrain.